The Political Cartel of Presidential Candidacy through Threshold Brings Up a Single Candidate - Saad, Muhammad; Sabrina, Dian Fitri; Sukardi, Sukardi (Universitas Airlangga, 2022)
AbstractThe practice of presidential nomination by using a threshold through political parties or coalitions of political parties in Indonesia is still carried out because Indonesia adheres to a multi-party system. However, the regulation regarding the threshold for presidential nomination is prone to political transactions between parties. The reason is that there is no equality of access to presidential nominations between new political parties and old political parties considering that political parties are a defining element of representative democracy (Political parties are a defining element of representative democracy), this practice threatens the rights of minority political parties and limits the emergence of presidential candidates. The threshold in the nomination of President based on the decision of the Constitutional Court of the Republic of Indonesia Number 74/PUU/XVII/2020 regarding the review of Law Number 7 of 2017 concerning Elections is referred to as an open legal policy which is the authority of the House of Representatives in forming the Law on Elections. This study aims to evaluate the application of the threshold in the nomination of President with the principle of justice. This research is a doctrinal research using a case approach and a law approach. This study was conducted by looking at the development of the application of thresholds in elections and the provisions stipulated in the Election Law. The results of the study indicate that it is necessary to establish an ideal implementation model based on the principle of justice in order to guarantee the rights of minority political parties and avoid the emergence of a single presidential candidate.Keywords: Political Cartel; President Threshold; Single Candidate.